Inhibitory Fc-Gamma IIb Receptor Signaling Induced by Multivalent IgG-Fc Is Dependent on Sialylation - Christopher Beneduce; Stephanie Nguyen; Nathaniel Washburn; John Schaeck; Robin Meccariello; Kimberly Holte; Daniel Ortiz; Anthony M. Manning; Carlos J. Bosques; Elma Kurtagic (Cells, 2023)
Immunoglobulin (IgG) Fc glycosylation has been shown to be important for the biological activity of antibodies. Fc sialylation is important for the anti-inflammatory activity of IgGs. However, evaluating the structure–activity relationship (SAR) of antibody Fc glycosylation has been hindered using simplified in vitro models in which antibodies are often displayed in monomeric forms. Presenting antibodies in monomeric forms may not accurately replicate the natural environment of the antibodies when binding their antigen in vivo. To address these limitations, we used different Fc-containing molecules, displaying their Fc domains in monovalent and multivalent fashion. Given the inhibitory role of Fc gamma receptor IIb (FcγRIIb) in autoimmune and inflammatory diseases, we focused on evaluating the impact of Fc sialylation on the activation of FcγRIIb. We report for the first time that in human cellular systems, sialic acid mediates the induction of FcγRIIb phosphorylation by IgG-Fc when the IgG-Fc is displayed in a multivalent fashion. This effect was observed with different types of therapeutic agents such as sialylated anti-TNFα antibodies, sialylated IVIg and sialylated recombinant multivalent Fc products. These studies represent the first report of the specific effects of Fc sialylation on FcγRIIb signaling on human immune cells and may help in the characterization of the anti-inflammatory activity of Fc-containing therapeutic candidates.